Utilization of Mangroves as Ecoprint Materials to Support Souvenir Products at the Ngulusenge Mangrove Tourism Attraction, Central Maitara Village, District of North Tidore - Rina, Rina; Abubakar, Salim; Subur, Riyadi; Sabar, Mesrawaty; Sunarti, Sunarti; Abubakar, Yuyun; Al Hadad, M. Said; Fadel, Ariyati H. (Jurnal Biologi Tropis, 2024)
Ecoprint is a term that comes from the words "eko", which means "ecosystem/nature", and "print", which means "print." The ecoprint printing method uses natural dyes to print flowers, twigs and leaves on fabric. This method begins by attaching mangrove leaves to cloth, then printing the leaves and stems on the cloth. The problems faced by community groups are the lack of public knowledge about the benefits of mangroves as a business opportunity, the lack of public knowledge about techniques for making mangrove leaf ecoprints. Mitra only knows that mangrove forests function to protect beaches from waves and the wood is used as firewood. Meanwhile, the use of mangroves as dyes for ecoprint products as tourist souvenir products and increasing business opportunities for the community is not yet known. The objectives of the PKM activity are: partners can find out about the benefits of mangroves as a business opportunity, apply appropriate technology in techniques for making ecoprints on mangrove leaves and obtain types of quality ecoprint product motifs that have high selling value. The training activity for making ecoprints by utilizing the potential of mangrove forest resources around the Ngusanlenge mangrove tourist attraction area went smoothly with high participant enthusiasm. Enthusiasm for the results of ecoprint products with a variety of patterns and motifs from the mangrove leaves used. PKM activities increase knowledge and improve the skills of the community and students in making ecoprints by utilizing the potential of mangrove forests and building community enthusiasm for entrepreneurship. The ecoprint products produced include bags, tablecloths, handkerchiefs and headscarves.